Endoscopic far-lateral supracerebellar infratentorial approach for resection of clival chordoma: case report - Han, Song; Bai, Yang; Sun, Xiaoyu; Chen, Ligang; Gao, Yang; Liu, Hongzhe; Li, Huanhuan (Frontiers in Oncology, 2024)
IntroductionThe surgery of clival chordoma remains one of the most formidable challenges for neurosurgeons because of its location at great depth in the cranium and proximity to critical neurovascular structures. Here, we describe the technique and feasibility of the purely endoscopic far-lateral supracerebellar infratentorial approach (EF-SCITA) for resection of an intradural clival chordoma.Case descriptionA 68-year-old women presented with sudden ptosis on the left side for two weeks. Imaging examinations revealed an upper-middle clival lesion that transgressed dural confines towards the posterior fossa, which was separated from the sphenoid cavity by an intact thin layer of membrane structure in front. For surgery, the EF-SCITA approach via suboccipital craniotomy was attempted for protecting surrounding neurovascular tissue and the membrane barrier under direct vision. The patients were placed in a “head-up” lateral park-bench position. With the endoscopic holder, endoscopic procedures were performed using standard two-hand microsurgical techniques by one surgeon. Tentorium incision allowed a working corridor toward the clival bulge through the crural cistern, without brain traction seen in traditional retrosigmoid approach. Efficient tumor debulking facilitated the exposure of surrounding critical structures, including ipsilateral CN III and superior cerebellar artery above, the brainstem and basilar artery posteriorly, as well as ipsilateral CN VI displaced laterally, and subsequent tumor separation from them. Step-wise tumor resection was performed within dural and bone confines. After significant tumor removal, the pituitary stalk could be visualized anteriorly, together with contralateral internal carotid artery and CN III. Postoperative MRI depicted gross total excision of the lesion. The patient on follow-up at one year had complete recovery of cranial nerve functions, without signs of cerebrospinal fluid rhinorrhea.DiscussionThis technique combines advantages of the posterolateral approach and endoscopy, allowing access to the upper-middle clivus with seemingly low risks of postoperative morbidity. It would be a safe and effective alternative for resection of this rare entity.